PENGARUH HARGA DAN PRODUKTIVITAS KELAPA SAWIT TERHADAP PENDAPATAN PETANI KELAPA SAWIT (Studi kasus di desa cahya negri kec.sukaraja kab.seluma) - Asad Hasan (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
This ttopic discusses and to find out about the effect of Oil Palm Price and Productivity on the Opinion of Oil Palm Farmers in Cahya Negri Village, Sukaraja District, Seluma Regency. The data of this study are primary data obtained directly from the first source either from individuals or individuals such as filling out questionnaires. The method used is multiple linear regression analysis assisted by software SPSS (Statistical Package For Social Science) 16. The results of the research conducted indicate that (1) the price of oil palm has a positive and significant effect on the income of oil palm farmers in Cahya Negri Village, Sukaraja District. Kab. Seluma. (2) oil palm productivity has a positive and significant effect on the income of oil palm farmers in Cahya Negri Kec. Sukaraja Kab. Seluma (3) oil palm prices and productivity have a significant effect on the income of oil palm farmers in Cahya Negri Kec. Sukaraja Kab. Seluma.